Human Resource Management Process - Jandeang, Burachat; Bubpata, Komsan; Kosolkittiampo, Assoc. Prof. Dr. Saowalak (Journal for Developing the Social and Community, 2019)
Human Resource Management is extremely important in driving organizational success. But executives do? Makes HRM success. And lead the organization to set goals that are sustainable. Important factors that make an organization successful man is one influenced that "man is the intellectual property of the organization that will lead the organization toward the achievement of goals. And the factors that make a significant difference in the race, "so organizations need a quality human resources management process. This is the duty of managing human resources to manage the human resource management efficiently as possible. Find out how to make people truly show its potential. The performance, quality and fully dedicated to the organization.